2016
DOI: 10.1002/2016ms000756
|View full text |Cite
|
Sign up to set email alerts
|

Global climate impacts of stochastic deep convection parameterization in the NCARCAM5

Abstract: In this study, the stochastic deep convection parameterization of Plant and Craig (PC) is implemented in the Community Atmospheric Model version 5 (CAM5) to incorporate the stochastic processes of convection into the Zhang‐McFarlane (ZM) deterministic deep convective scheme. Its impacts on deep convection, shallow convection, large‐scale precipitation and associated dynamic and thermodynamic fields are investigated. Results show that with the introduction of the PC stochastic parameterization, deep convection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…At different resolutions, the overall geographical distribution of global total precipitation between the CTL and EXP is comparable, with more overestimated tropical ocean precipitation in EXP than that in CTL. The increased total precipitation in EXP is mainly from the increase of grid‐scale precipitation (Wang & Zhang, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…At different resolutions, the overall geographical distribution of global total precipitation between the CTL and EXP is comparable, with more overestimated tropical ocean precipitation in EXP than that in CTL. The increased total precipitation in EXP is mainly from the increase of grid‐scale precipitation (Wang & Zhang, ).…”
Section: Resultsmentioning
confidence: 99%
“…With these sensitivity tests and the above three EXP simulations, the resolution dependence of simulated precipitation using the stochastic convection scheme can be investigated. No sensitivity tests are performed for temporal averaging as Wang and Zhang () showed that its impacts are negligible. All simulations except for CTL and EXP simulations at 2° resolution are run for 3 years from 1990 to 1992 with the same vertical resolution of 30 levels.…”
Section: Model Experiments and Evaluation Datamentioning
confidence: 99%
See 3 more Smart Citations